Women’s Right to Abortion After Overturning Roe v Wade: Contextualizing the USA and Bangladesh - Jamil, Arif; Ibn Masud, Md Rafi; Chowdhury, Sal Sabil; Chowdhury, Ahmed Ragib (Dhaka University Law Journal, 2025)
The paper brings forward a critical analysis aiming to address the ramifications of overturning the judgment of Roe v Wade in the pronouncement of Dobbs v Jackson Women’s Health Organization by the United States Supreme Court. The everlasting debate of pro-life v. pro-choice is highly unlikely to be resolved anytime soon. The domestic legal frameworks on abortion are underdeveloped in most countries, and the discrepancies among different legal frameworks make the recognition of right to abortion significantly challenging. Without a binding international legal instrument, the implementation of safe and legalized abortion is never guaranteed. While multiple countries took a progressive approach inspired by Roe, the recent overturning of such in 2022 creates the burning question of its ramifications in the US and beyond. Based mostly on doctrinal research and a ‘survey numerical summary’ conducted amongst 33 respondents studying or completing the course of ‘Law and Ethics in Life Sciences,’ this paper sets out to explore one fundamental question: Do we need a universal standard to ensure women’s right to abortion in the post-Roe era? Besides delving into a critical analysis of Dobbs, the paper analyses pro-life and pro-choice advocacy strategies, different domestic and regional frameworks, and relevant human rights implications. Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 25-62